Konsep Kecerdasan Intelektual dalam Al-Qur’an dan Implikasinya bagi Pendidikan Islam - David Ricardo; Ansorul Alim; Dwi Ratnasari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
This study aims to examine the concept of intellectual intelligence from the perspective of the Qur’an and its implications for the development of contemporary Islamic education. The background of this research is rooted in the tendency of modern education to emphasize rational–cognitive aspects while neglecting spiritual and moral dimensions. This study employs a qualitative approach with a library research design, utilizing thematic analysis of Qur’anic verses, classical and contemporary tafsir works, and relevant scholarly literature. The findings reveal that intellectual intelligence in the Qur’an is understood holistically through the concepts of ‘aql, tafakkur, tadabbur, and tafaqquh, and is represented in the characteristics of ulul albab, qaum ya‘qilun, and ulul abshar. Qur’anic intellectual intelligence is not value-neutral but is integrated with God-consciousness and moral responsibility. The implications of this study emphasize the need for Islamic education to develop intellectual capacity in a critical, reflective, and value-oriented manner through dialogical learning, integrative curricula, and the role of educators as intellectual and moral facilitators. These findings reinforce the urgency of renewing the paradigm of Islamic education that balances intellect, faith, and morality.